Surgery plus chemotherapy versus chemotherapy alone in primary intestinal lymphoma: a meta-analysis - Yefei Shu (SAGE Publishing, 2021)
Objective Primary intestinal lymphomas (PILs) are uncommon tumors, but their incidence is increasing. Currently, their management is centered around systemic treatments, such as chemotherapy and radiotherapy, whereas surgery is restricted to selected indications. This meta-analysis aimed to evaluate the role of surgery in PIL treatment. Methods We collected publications comparing surgery plus chemotherapy versus chemotherapy alone in patients with PIL from 2000 to 2021. All trials analyzed the summary odds ratios (ORs) of endpoints, including the 5-year overall survival (OS), 3-year OS, and 3-year progression-free survival rates. Combined pooled ORs were analyzed using fixed- or random-effects models according to heterogeneity. Results Six studies were included. Compared with chemotherapy alone, surgery plus chemotherapy was associated with significantly higher 5-year OS [OR = 4.88, 95%confidence interval (CI) = 1.91–12.44, Z = 3.32], 3-year OS (OR = 3.83, 95%CI = 2.33–6.30, Z = 5.30), and 3-year progression-free survival (OR = 3.51, 95%CI = 2.20–5.58, Z = 5.29). Conclusions Surgery plus chemotherapy was associated with better outcomes than chemotherapy alone, especially in the early stages. Therefore, surgery plus chemotherapy may be the preferred strategy for appropriately selected patients with PIL. The protocol for this systematic review was registered at INPLASY (INPLASY202180102) and is available in full ( https: //doi.org/10.37766/inplasy2021.8.0102 ).